1983
DOI: 10.1902/jop.1983.54.7.389
|View full text |Cite
|
Sign up to set email alerts
|

Cementogenesis and Soft Tissue Attachment After Citric Acid Treatment in a Human: An Electron Microscopic Study

Abstract: The four maxillary incisors and two maxillary premolars of a 25-year-old male patient were used to study epithelial and connective tissue attachment 67 days and 164 days after flap surgery and cutting of an horizontal intradentinal groove near the buccal cervical region. Three teeth were topically conditioned for 3 minutes with citric acid pH = 1. The three other teeth were used as controls. The histologic examination was carried out in double-blind conditions; the examiners did not know which specimens were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0
3

Year Published

1985
1985
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(21 citation statements)
references
References 15 publications
3
15
0
3
Order By: Relevance
“…It probably stabilizes and provides strength to the union between the collagenous matrices of the two tissues. In this respect our findings are analogous to those of authors who have studied healing processes in the periodontium and found that, following the removal of the cementum layer and treatment of the exposed dentin with the demineralizing agent citric acid, splicing of collagen fibers may occur between demineralized dentin and newly formed collagen fibrils by gingival and periodontal fibroblasts (Frank et al, 1974(Frank et al, ,1983Garrett et al, 1978;Ririe et al, 1980;Selvig, 1983).…”
Section: Effects Of Hebp On Acellular Cementum Formationsupporting
confidence: 89%
“…It probably stabilizes and provides strength to the union between the collagenous matrices of the two tissues. In this respect our findings are analogous to those of authors who have studied healing processes in the periodontium and found that, following the removal of the cementum layer and treatment of the exposed dentin with the demineralizing agent citric acid, splicing of collagen fibers may occur between demineralized dentin and newly formed collagen fibrils by gingival and periodontal fibroblasts (Frank et al, 1974(Frank et al, ,1983Garrett et al, 1978;Ririe et al, 1980;Selvig, 1983).…”
Section: Effects Of Hebp On Acellular Cementum Formationsupporting
confidence: 89%
“…Previous studies in dogs (Ride et al 1980), squirrel monkeys . and a human (Frank et al 1983) have reported new connective tissue attachment to demineralized root surfaces without formation of cementum. The study utilizing dogs (Ririe et al 1980).…”
Section: Discussionmentioning
confidence: 97%
“…reported initial continuity between the collagen of the demineralized dentin and adjacent connective tissue at 14 days, however, this attachment became reinforced by deposition of new cementum by 42 days. In the human study (Frank et al 1983), new attachment to dentin was described as a mineralization of decalcified dentin collagen which was spliced with newly secreted collagen. The longest observation period in the other animal studies ) was 21 days, and this may not be a long enough time period for cementum formation to occur (Stallard & Hiatt 1968, Listgarten 1972, Poison & Caton 1982.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated minimal regeneration in the apical region of the periodontal lesion following periodontal surgery. [1][2][3][4][5][6][7][8] There is no significant correlation between defect depth and CAL gain following open debridement alone, and the majority of defects showed a gain of only 1 to 2 mm of clinical attachment or bone. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] In order to boost regenerative potential, particularly bone fill, osseous grafting with cortical chips, 29,30 osseous coagulum, 31 cancellous bone from the maxillary tuberosity or healing extraction site, [32][33][34] and autogenous iliac crest [35][36][37][38][39][40][41] have documented mean bone repair measurements of 2 to 4 mm 32,33,35,42 and histologic evidence of regeneration.…”
Section: Introductionmentioning
confidence: 99%